Blocking tumor escape in hematologic malignancies: The anti-PD-1 strategy. Issue 1 (January 2015) - Bryan, Locke J.; Gordon, Leo I.
Abstract Immunotherapy remains an important tool for treatment of hematologic malignancies. The Programmed Death-1 (PD-1) immune checkpoint pathway has emerged as a mechanism of tumor evasion from the anti-tumor immune response. The recent development of anti-PD-1 monoclonal antibodies has offered a targeted approach to cancer therapy. Several agents are in various stages of development and have shown clinical responses across a broad spectrum of both solid and hematologic malignancies. The use of anti-PD-1 therapy in hematologic malignancies is limited but has demonstrated clinical responses in relapsed/refractory disease following multiple lines of therapy. PD-1 blockade may reduce relapse rates for patients who fail to obtain a complete remission prior to autologous hematopoietic cell transplant. The role of the PD-1 pathway for tumor escape is reviewed. We explore the use of anti-PD-1 therapy in hematologic malignancies. The proposed mechanism of PD-1 blockade as a modulator of the innate and acquired immune response is considered. Finally, the challenges of anti-PD-1 therapy and the future direction of investigation in this area are reviewed.